Corpus Callosum Growth and Neurodevelopmental Outcome Are Negatively Influenced by Systemic Infection in Very Low-Birth-Weight Infants - Korček, Peter; Korčeková, Zuzana; Berka, Ivan; Kučera, Jáchym; Straňák, Zbyněk (Journal of child neurology, 2021)
Systemic infection may negatively modulate the development of cerebral white matter and long-term outcome of neonates. We analyzed the growth of corpus callosum (using cranial ultrasonography) and neurodevelopment (Bayley Scales of Infant Development, Third Edition) in 101 very low-birth-weight newborns. We observed significantly reduced corpus callosum length at 3 months of corrected age (44.5 mm vs 47.7 mm, P = .004) and diminished corpus callosum growth (0.07 mm/d vs 0.08 mm/d, P = .028) in infants who experienced systemic infection. The subgroup exhibited inferior neurodevelopmental outcomes with predominant motor impairment. The results suggest that length and growth of corpus callosum might be affected by systemic inflammatory response in preterm newborns. The changes in corpus callosum can contribute to adverse neurodevelopment at 2 years of corrected age. Serial ultrasonographic measurements of the corpus callosum may be suitable to identify preterm infants with increased risk of neurodevelopmental impairment.
Keywords: corpus callosum; Female; Infant; předškolní dítě; novorozenec; ultrasonografie; ženské pohlaví; sepse; Sepsis; Infant, Very Low Birth Weight; lidé; Infant, Newborn; Causality; novorozenec nedonošený; Ultrasonography; následné studie; Infant, Premature; kauzalita; Corpus Callosum; neurovývojové poruchy; kohortové studie; Cohort Studies; prospektivní studie; Follow-Up Studies; Male; kojenec; Prospective Studies; novorozenec s velmi nízkou porodní hmotností; Child, Preschool; Neurodevelopmental Disorders; mužské pohlaví; Humans